2004
DOI: 10.1108/02641610410538559
|View full text |Cite
|
Sign up to set email alerts
|

License to Deny? Publisher restrictions on document delivery from e‐licensed journals

Abstract: The licensing of electronic journals is affecting interlibrary loan and document delivery services. This article reports on a survey done in 2003 at 13 large research libraries on how licensing affects both the lending and borrowing operations at those libraries. A brief history on copyright legislation and guidelines as they relate to ILL are provided as background on how licenses can undermine the copyright support libraries have needed to provide the services users require. ILL data is presented to illustra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…In 2004, Lynn Wiley, from the University of Illinois UrbanaChampaign in Urbana, published an excellent discussion about interlibrary lending and e-journal licenses. 3 It was interesting to note that not all of the limitations on interlibrary library loan were because of the license agreement. Libraries responding to Wiley's survey indicated other reasons for not filling requests from electronic versions of journals, including difficulty accessing the license information easily and as a result, making decisions to fill requests only from print versions of journals even if the electronic version was available.…”
Section: The Interlibrary Loan Factormentioning
confidence: 99%
“…In 2004, Lynn Wiley, from the University of Illinois UrbanaChampaign in Urbana, published an excellent discussion about interlibrary lending and e-journal licenses. 3 It was interesting to note that not all of the limitations on interlibrary library loan were because of the license agreement. Libraries responding to Wiley's survey indicated other reasons for not filling requests from electronic versions of journals, including difficulty accessing the license information easily and as a result, making decisions to fill requests only from print versions of journals even if the electronic version was available.…”
Section: The Interlibrary Loan Factormentioning
confidence: 99%
“…Gadd et al (2003); Antelman (2006); and Coleman (2007) have analysed license agreements regarding the issue of author selfarchiving. A study by Wiley (2004) on publisher restrictions on document delivery opined that library staff is being restricted by the publisher agreements. Coleman (2007) analysed the self-archiving and the copyright transfer agreements of 52 ISI-ranked library and information science journals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, it is laborious to maintain and update the information required: the Okamoto study found that the checking tasks and lack of knowledge very often lead ILL librarians refusing to supply e-journal contents (Okamoto, 2012). Wiley notes succinctly that "the license checking that is required inhibits fulfilment more than the licenses restrictions do themselves" (Wiley, 2004).…”
Section: Identifying the Proper Licencementioning
confidence: 99%